KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONALISME GURU - Nunuk Anggraini; Muhammad Alamsyah Putra; Mardiyah Mardiyah (Intelegensia : Jurnal Pendidikan Islam, 2023)
Leadership is the main determinant of the process of the birth of a nation, the dynamics of education and the effectiveness of leadership. The principal is a person who has great influence on the school. As a supervisor, the principal participates in the management of his educational resources. Writing this article uses a type of qualitative research with the method of literature study. The purpose of writing this article is to find out the role of the principal in developing extraordinary teacher professionalism, so that teachers can be professional in educating students. The results of the school principal's research must carry out their duties according to their obligations, policies and be responsible. The responsibilities of the principal include the following for professional teachers: the principal as an educator, the principal as a manager, the principal as a supervisor, the principal as a leader, the principal as an administrator, the principal as a motivator, and the principal as a creator of the environment Work. The following abilities are needed by every educator to become a professional teacher: knowledge, understanding, abilities, attitudes, values and interests. A quality teacher can cultivate high-quality, future-ready students.